Health education for the prevention of sexually transmitted infections in the population over 18 years of age (Research, Society and Development, 2024)
The study portrays young people's knowledge about sexually transmitted infections and how they approach this topic in relation to education for prevention, thus laying the foundations for the implementation of prevention measures in public health, making it possible to improve the quality of life of young people. population, especially young people. Objective: To correlate sexual education with the prevention of sexually transmitted infections in the population. Methodology: This research is characterised by quantitative, descriptive and longitudinal methods. With volunteers aged 18 and over, of both sexes, who answered an adapted questionnaire from the Survey of Knowledge, Attitudes and Practices of the Brazilian Population (PCAP) 2013, with 37 questions from a multiple-choice evaluation form, applied in virtual form through the Google Forms platform via a link shared through social networks: Facebook, Instagram, WhatsApp. It is concluded that the data obtained and the prevalence of key articles highlighted the lack of preparation of educators and health professionals in sexual education for the population, in the prevention of sexually transmitted infections, which demonstrated the need for innovations in the way of education, which requires professionals to be trained to interact with different cultures, beliefs, sexual orientation, age group and economic conditions.